The cryptography technology usage in message system: Online shoppers perspective - Othman, Azrina; Mohamad, Norhidayah; Mohd Din, Adilah; Abdul Rahman, Nik Adzrieman (Human Resource Management Academic Research Society, 2024)
This research explores the essential role of cryptography in securing messaging systems within online shopping platforms, with a focus on consumer perspectives in Malaysia. As online shopping becomes increasingly prevalent, the need for secure communication to protect sensitive information and maintain consumer trust is paramount. The study utilizes the Technology Acceptance Model (TAM) to examine factors influencing the adoption of cryptography technology among online shoppers. A survey of 150 Shopee users was conducted to gather insights on their perceptions of the technology's usefulness, ease of use, confidentiality, and non-repudiation. Data analysis using SPSS, including descriptive statistics, Pearson correlation, and linear regression, revealed that all four factors significantly impact the adoption of cryptography, with non-repudiation being the most influential. The findings suggest that consumers prioritize the assurance that their messages cannot be altered or denied, underscoring the need for strong cryptographic protections in online shopping platforms. However, the study faced limitations due to the COVID-19 pandemic, which restricted data collection to online methods. Future research should broaden the scope by including a more diverse demographic and geographical representation and incorporating in depth interviews with industry experts. These steps would provide further insights into the effectiveness of different cryptographic methods across various platforms and industries.